Development of A Direct Conductive Coupled Multi-Input Phase-Shifted Full-Bridge DC-DC Converter (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Hybrid energy system is commonly employed in renewable energy systems to bridge the gap of non-availability of one power source with the others. In this work, a direct conductive electrical circuit connection topology for realizing multiple power source synchronization in the hybrid energy system is proposed. A three-input power sources integration scheme was realized via forward-conduction bidirectional blocking switch which serves input to the common power conversion stage of phase-shifted full-bridge DC-DC converter to boost the synchronized common bus voltage. An average current sharing controller is designed for the multiple parallel power sources to ensure equal load sharing when all the sources operates on the same and different voltage level.Â  In this study, a 3-kW rating hybrid energy system was implemented in Simulink environment to investigate the multiple source integrator, the current sharing capability, and the common power conversion stage performance. The system ensured equal load sharing, allowed individual and simultaneous power transfer from the multiple sources to the load under the same and different operating supply voltage level.